2010
DOI: 10.1002/ppul.21327
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between infant lung function and the risk of wheeze in the preschool years

Abstract: Rationale-Premorbid infant lung function predicts childhood wheeze, but it is unclear whether lower infant lung function is most closely associated with atopic or non-atopic preschool wheeze.Objective-To examine the association between premorbid infant lung function and preschool wheeze according to atopic or non-atopic wheeze phenotype. Additionally, to explore the relations of ADAM33 polymorphism with lung function during infancy, preschool wheeze and atopy.Methods-Infant lung function was measured in147 hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 29 publications
1
29
0
3
Order By: Relevance
“…While previous studies have demonstrated reduced lung function soon after birth in individuals who wheeze in infancy [7,8], the relationship between infant lung function and wheezing disorders beyond infancy is less clear [5,6]. The findings of VAN DER GUGTEN et al [1] in conjunction with those from the Southampton Women's Survey provide evidence that structural airway impairments in infancy may differentially predict asthma and wheeze in childhood.…”
Section: Infant Lung Function and Wheeze In Later Childhood In The Sosupporting
confidence: 60%
“…While previous studies have demonstrated reduced lung function soon after birth in individuals who wheeze in infancy [7,8], the relationship between infant lung function and wheezing disorders beyond infancy is less clear [5,6]. The findings of VAN DER GUGTEN et al [1] in conjunction with those from the Southampton Women's Survey provide evidence that structural airway impairments in infancy may differentially predict asthma and wheeze in childhood.…”
Section: Infant Lung Function and Wheeze In Later Childhood In The Sosupporting
confidence: 60%
“…Although most of these studies concluded that lower early lung and airway function were associated with subsequent development of infant wheezing [1][2][3][4][5], the association between neonatal lung function and wheezing symptoms and asthma in childhood is not consistently found [6][7][8][9]. One possible explanation for the inconsistent findings could be that because of the difficulties in measuring infant lung function, most studies had a small sample size.…”
Section: Introductionmentioning
confidence: 59%
“…Again, these children continued to have lower levels of lung function at the ages of 11 and 16 years relative to those who had never wheezed. Hereditary of asthma, female gender, atopy, inhalant allergens, IgE level at 9 months of age, exposure to tobacco smoke, viral infection, and early animal exposure have been shown to have important effects on lung function and bronchial hyperresponsiveness [6,[14][15][16][17][18][19][20][21][22].…”
Section: Examples Of Diseases With Obstructive Lung Diseasementioning
confidence: 99%
“…Younger patients can deliver this volume faster than adults, and evaluation of the FEV 0.4 , FEV 0.5 , or FEV 0.75 may be necessary [3,6]. Patients are usually studied in a standing or seated position to optimize lung function.…”
Section: Spirometrymentioning
confidence: 99%